Analisis Tindak Tutur Lokusi dalam Siaran Langsung TikTok Anies Baswedan “Menyapa Masyarakat Lewat Media Sosial TikTok” Januari 2024 - Ardani Tangguh Waskito; Dea Suryaningtyas Mustika Hapsari; Elfara Desfiona; Serlys Kusumawati; Rania Riza Aulia; Asep Purwo Yudi Utomo; Nurnaningsih Nurnaningsih (Jurnal Kajian dan Penelitian Umum, 2024)
A locational act is an act of speaking that presents something in the form of a sentence with a meaning that can be easily understood. There are several kinds of locus, namely declarative, interrogative, and imperative. During the live broadcast, Anies Baswedan used the types of declarative, imperative, and interrogative localization. From this analysis, the researchers wanted to understand and learn how the tactics used by Anies Baswedan in communicating with the public through social media Tiktok. In this study, the author used a qualitative approach with a type of descriptive research. The data was obtained from TikTok's live broadcast of Anies Baswedan, which contains a list of locations. Data collection methods involve sliding and recording techniques, with steps such as watching videos, interpreting rows, recording locations, and identifying data. Data analysis techniques use data reduction, data presentation, and verification to reach credible provisional conclusions. The results of the analysis revealed a positional observation, a declarative observation consisting of 66 observations, an interrogatory observation comprising 39 observations, and an imperative confirmation of 22 observations. With this analysis, it is expected that the reader will be able to interpret and classify the type of conduct at these locations.